The possibility of using frozen table grapes in the production of functional food products - A. V. Tarasenko; L. Y. Rodionova (Новые технологии, 2023)
The article is devoted to the research in the field of the use of frozen grapes in the production of functional products. The main tasks are to substantiate the technological significance of frozen table grapes for the development of recipes for functional products and to investigate the influence of negative temperatures on the change in the quality indicators of raw materials. The objects of the research are 5 table varieties of grapes grown on plantations of the peasant farm of the Dinskoy district of Krasnodar. At the Department of Technology of Storage and Processing of Crop Products of the Kuban State Agrarian University named after I.T. Trubilin, experimental studies of the qualitative characteristics of fresh grapes have been carried out in order to study and confirm the prospects for using frozen grapes for the production of functional products. To perform the research, standard physicochemical and organoleptic methods of analysis, generally accepted in the food industry, have been used. The grape berry is a source of nutrients that the body needs to maintain a full and active lifestyle when consumed fresh: anthocyanins, pectins, vitamins and minerals.The disadvantage of replenishing these nutrients is the short period of consumption of fresh grapes. To study the technological qualities of grapes, varieties with different ripening periods have been studied.Freezing as a preservation method allows these products to be consumed throughout the year. The methods of physical and chemical analysis have been used to determine the indicators of the biochemical composition of fresh and defrost grapes, confirming their biological and nutritional value. It has been established that shock freezing of grapes with subsequent defrosting allows preserving biologically valuable components of the chemical composition of the objects under study, which makes it possible to develop healthy food products from frozen table grapes.